WHY IS NOT RECOMMENDABLE EVADING? A MODEL OF GAME THEORY APPLIED TO THE PROBLEMS OF EVASION. - Serrano Galán, Cintia Estefanía; Andrade Rosas, Luis Antonio (Memorias del Concurso Lasallista de Investigación, Desarrollo e innovación, 2018)
The decision about tax declaration is a decision under uncertainty. The failure to report one´s full income to the government does not induce automatically to a penalty, it takes time, investigation, and extra costs. In this project, we are considering a simple model where this decision is the only one with which the taxpayer is concerned. So, we showed the strategies that the government can apply to avoid the wrong tax return.